Brief Report: Low‐Barrier Buprenorphine Initiation Predicts Treatment Retention Among Latinx and Non‐Latinx Primary Care Patients. Issue 5 (28th June 2019) - Lee, Christina S.; Rosales, Robert; Stein, Michael D.; Nicholls, Mariana; O'Connor, Bridget M.; Loukas Ryan, Vanessa; Davis, Elizabeth A.
Abstract : Background and Objectives: Patients are at risk of dropout while waiting for buprenorphine treatment. Study goals are to compare 3‐month retention in two different methods to buprenorphine initiation among persons with opioid use disorder. Methods: We compared 3‐month treatment retention rates of low‐barrier buprenorphine initiation (i.e., rapid induction) ( n =58) or a traditional method of buprenorphine initiation ( n = 45) for persons with opioid use disorder seen at an urban community health center. Results: Logistic regression revealed that low‐barrier initiation had 11.11 greater odds of retention compared with traditional methods ( p <0.001). Latinx patients benefited more than non‐Latinx patients (OR = 14.79, p =.039). Discussion and Conclusions: All patients were more likely to be retained using low‐barrier initiation. A significantly larger effect on retention among Latinx patients was observed. Scientific Significance: Rapid buprenorphine initiation increases treatment retention which improves treatment outcomes for persons with opioid use disorder. Study findings support a less restrictive services model that is even more effective for Latinx patients. (Am J Addict 2019;28:409–412)